Creating security to finance waqf property development in Malaysia: Issues and solutions - Syed Abdul Kader, Sharifah Zubaidah; Mohamad, Nor Asiah (Emerald Publishing Ltd, 2019)
Legal and shari’ah issues abound in creating security to finance waqf property development in Malaysia for it involves integrating the shariah concept of waqf with requirements of Malaysian land law as well as the requirements of modern finance under civil law. Banks and financial institutions will not generally finance property development without any form of security for the loan. The best type of security transaction under Malaysian land law is to create a charge on the land under the National Land Code 1965, rendering the land liable as a security which upon default of the chargor, would entitle the chargee to seek statutory remedies including sale of the land. Such may not be feasible for waqf properties due to the inalienable nature of such properties. Due to the remedy of sale of the land upon default, the same issues would arise in regard to other types of securities like a lien and a loan agreement cum assignment. There is therefore a need to diversify the available options in creating security over waqf property. What are the existing shari’ah restrictions on waqf property? Do these restrictions affect the creation of security over waqf lands under conventional Malaysian land law? What are the legal and shariah issues relating to creating a charge over waqf lands? What are some feasible options? Initial findings are that creating a charge on a lease of waqf land as well as resorting to a hybrid form of a traditional security transaction in Malaysia called ‘Jual-Janji’ may hold some answers. Through doctrinal legal research and content analysis, this paper explores these issues and recommends feasible solutions.